Review on Xenotransplantation - Basnet, S; Kafle, D; Aryal, B (Journal of Chitwan Medical College, 2013)
There is an increasing interest in the potential clinical application of xenotransplantation. This interest derives in part from the need to identify a more abundant source of organs for transplantation and in part from rapid progress in understanding the cellular and molecular changes that contribute to hyperacute and acute vascular xenograft rejection. Recent areas of progress in understanding the immunological hurdles to xenotransplantation include the characterization of xenoreactive antibodies and the antigens they recognize, the role of complement regulatory proteins in immune recognition, the mechanism of complement activation in a xenograft, and the pathophysiologic changes in endothelial cells caused by the activation of complement. Several approaches have been proposed or used to prevent or reduce the xenogeneic immunologic rejection response, including immunosuppression, genetic engineering, complement inhibitors, and physical barriers. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8627 Journal of Chitwan Medical College 2013; 3(3): 1-3